Oral manifestations associated with concurrent CMV and HSV-1 in children with cerebri abses: rare case report: Manifestasi oral infeksi CMV dan HSV-1 pada anak penderita abses serebri: laporan kasus langka - Rahmi Harmiyati; Tenny Setiani Dewi (Makassar Dental Journal PDGI Makassar, 2022)
Herpes simplex virus-1 (HSV-1) and cytomegalovirus (CMV) are members of the human herpes viridae (HHV) family that can infect and give oral manifestations. This case report aims to discuss the oral manifestations of HSV-1 and CMV infection in a child with cerebral abscess. A 7-year-old boy was referred from the Department of Pediatrics to the Department of Oral Medi-cine with complaints of sore mouth sores, especially when eating, three days ago.Extraoral examination revealed that the lips were dry and peeling. Intraoral examination on the dorsum and lateral of the tongue, buccal mucosa and labialmucosa there is white plaque spread, can be scraped and leave an area of ​​erythema. Many ulcers were found, shallow oval in shape, yellowish white in color,surrounded by a diffuse reddish border, varying in size 0.1-0.5 cm in the oropharynx, tonsils, and other oral mu-cosa. The blood laboratory examinations showed a decrease in the value of leukocytes, albumin, creatinine, and sodium, while the monocyte and SGOT values ​​were high, with anti-HSV-1 IgG and reactive anti-CMV IgG. The established diagnosis was acute pseudomembranous oral candidiasis with intraoral HSV-1 and CMV infection. The treatment given is cleaning the entire surface of the oral cavity by gargling with 1% povidone iodine mouthwash 2 times a day, an hour break followed by administration of 1 mL oralsuspension of nystatin 4 times a day, and applying a thin layer of vaseline to the lips 2 times a day. The oral lesions healed on day-10. It was concluded that the oral manifestations can occur in patients with HSV-1 and CMV virus infections.